Trade liberalisation and child wellbeing: potential impacts of the Peru-US free trade agreement - Villar, Eliana (2005)
Trade liberalisation’s potential to promote national economic growth is internationally acknowledged. It can help countries to exploit their comparative advantage in the production of regionally specific goods and take advantage of larger markets for products that have limited local demand. Liberalisation may also generate economies of scale, increase efficiency and lower production costs. Countries can remain competitive – against a background of proliferating multilateral and bilateral trade agreements – by gaining the same access to large trading partners as their regional competitors.